Branched-chain amino acids and insulin resistance in type 2 diabetes: from metabolic dysregulation to therapeutic targets - Mei, Jie; Yang, Fu-yuan; Gong, Quan (Frontiers in Endocrinology, 2026)
Branched-chain amino acids (BCAAs) are a class of amino acids characterized by a branched aliphatic side chain, and they play critical physiological roles in humans, including protein synthesis, metabolic regulation, and immune system maintenance. Beyond serving as fundamental building blocks for protein biosynthesis, BCAAs and their metabolites also function as signaling molecules that regulate a variety of physiological processes, notably insulin secretion. Accumulating evidence indicates that plasma BCAAs levels are markedly elevated in patients with type 2 diabetes (T2DM), a phenomenon that may result from impaired activity of key enzymes in the BCAAs catabolic pathway, leading to metabolic dysregulation. It is widely recognized that BCAAs can activate the mTOR signaling cascade, thereby affecting insulin receptor sensitivity. In addition, aberrant BCAAs metabolism has been closely linked to alterations in the gut microbiota, which may further aggravate insulin resistance (IR). Taken together, dysregulated BCAAs metabolism may represent a critical mechanism underlying IR in T2DM. Therefore, this review summarizes current knowledge on BCAAs metabolism, explores its potential roles in the pathogenesis of IR in T2DM, and highlights emerging therapeutic strategies to reduce IR by targeting BCAAs metabolism.